The Protective Effect of Naringenin on Airway Remodeling after Mycoplasma Pneumoniae Infection by Inhibiting Autophagy-Mediated Lung Inflammation and Fibrosis - Yan Lin; Dan Tan; Qianna Kan; Zhen Xiao; Zhiyan Jiang (Mediators of Inflammation)
Our previous study has shown that Chinese medicine, Qingfei Tongluo formula (QTF), has a significantly therapeutic effect to Mycoplasma pneumoniae (MP) pneumonia (MPP). The aim of this study was to investigate the therapeutic effect and mechanism of naringenin (NRG) on MPP which was an important component of QTF. Here, we studied 124 children with or without MPP and compared inflammatory cytokines and fibrinogen-related protein expression with enzyme-linked immunosorbent assay. We also employed a BALB/c mouse model of MPP and divided the mice into three groups: ctrl (normal control mice), MPP (MP-infected mice), and MPP + NRG (MP-infected mice treated with NRG). BEAS-2B cells were used to confirm the relationship between autophagy, inflammation, and fibrosis. The results show proinflammatory cytokines (interleukin- [IL-] 6, IL-1β, and tumor necrosis factor-α), and transforming growth factor beta (TGF-β) expression was significantly increased after MP infection from both clinical and animal experiment. In vivo experimental confirmation showed that NRG treatment decreased MPP-induced lung injury in mice by inhibiting autophagy-mediated inflammatory cytokine expression and pulmonary fibrosis. In vitro experiments confirmed it. These results indicate that NRG treatment suppressed the inflammatory response and pulmonary fibrosis by inhibition of autophagy after MP infection.